A Macromolecule Reversing Antibiotic Resistance Phenotype and Repurposing Drugs as Potent Antibiotics. Issue 17 (21st July 2020) - Ding, Xin; Yang, Chuan; Moreira, Wilfried; Yuan, Peiyan; Periaswamy, Balamurugan; de Sessions, Paola Florez; Zhao, Huimin; Tan, Jeremy; Lee, Ashlynn; Ong, Kai Xun; Park, Nathaniel; Liang, Zhen Chang; et al.
Abstract: In order to mitigate antibiotic resistance, a new strategy to increase antibiotic potency and reverse drug resistance is needed. Herein, the translocation mechanism of an antimicrobial guanidinium‐functionalized polycarbonate is leveraged in combination with traditional antibiotics to afford a potent treatment for drug‐resistant bacteria. Particularly, this polymer–antibiotic combination approach reverses rifampicin resistance phenotype in Acinetobacter baumannii demonstrating a 2.5 × 10 5 ‐fold reduction in minimum inhibitory concentration (MIC) and a 4096‐fold reduction in minimum bactericidal concentration (MBC). This approach also enables the repurposing of auranofin as an antibiotic against multidrug‐resistant (MDR) Gram‐negative bacteria with a 512‐fold MIC and 128‐fold MBC reduction, respectively. Finally, the in vivo efficacy of polymer–rifampicin combination is demonstrated in a MDR bacteremia mouse model. This combination approach lays foundational ground rules for a new class of antibiotic adjuvants capable of reversing drug resistance phenotype and repurposing drugs against MDR Gram‐negative bacteria. Abstract : Guanidinium‐functionalized polycarbonates reverse antibiotic resistance phenotype and improve antibiotic potency via intracellular protein precipitation, gene binding, and subsequent reactive oxygen species generation. Importantly, the polymer allows for the effective repositioning of rifampicin and auranofin meant for Gram‐positive bacteria and arthritis, respectively, to be highly effective against multidrug‐resistant Gram‐negative bacteria both in vitro and in vivo.